Influence of particle size on the properties of Pt-Ru/C catalysts prepared by a microemulsion method - Godoi, Denis Ricardo Martins de [UNESP]; Perez, Joelma; Villullas, H. Mercedes (Electrochemical Soc Inc, 2007)
Pt-Ru/C nanocatalysts were prepared by a microemulsion method using different values of water/surfactant molar ratio in order to get different particle sizes. Crystallite sizes and structural properties were determined by X-ray diffraction. Particle size and distribution were characterized by transmission electron microscopy and average composition was determined by energy-dispersive X-ray analysis. Thermogravimetric analysis was used to estimate the amount of supported metals. Differential scanning calorimetry measurements indicated the presence of hydrous ruthenium oxides in the as-prepared catalysts. Results for the oxidation of adsorbed CO as well as for methanol oxidation revealed significant differences in the behavior of the prepared catalysts. All together, the results demonstrate that the variation of particle size produces changes in other properties of the Pt-Ru/C catalysts and that to establish direct correlations between electrocatalytic activity and particle size is not possible because the effects of the different parameters cannot be separated. (c) 2007 the Electrochemical Society.